MOTIVATION: THE HEART OFLEADERSHIP - Abdurrahman Adrian; Anita Firdaus, Checilya Anastasya Panggabean, Cut Fara Vhiqia Yusuf, Salman Rawin Siregar, Wiwiek Me (International Journal of Teaching and Learning, 2025)
Leadership It is not about commanding or giving orders but inspiring and motivating teams toward the achievement of exceptional output. This will form that bond driving this success engine, whose potential is unimaginable. This paper will discuss the role of motivation in leadership and types of leadership motivation. The method used is qualitative literature study approach (library research). The result is that qualitative research is done with a research design whose findings are not obtained through statistical procedures or in the form of counts, but rather seek to reveal phenomena in a holistic- contextual manner by collecting data from natural settings and making use of researchers as key instruments. Data collection is carried out by finding sources and reconstructing from different sources such as books, journals, articles, and existing research. This qualitative research design can be adopted as a method in research because the design is described in an elucidative way that researchers and academics can easily understand.